Pengaruh Budaya Organisasi terhadap Kinerja Karyawan Bagian Penjualan pada PT. Agung Automall Paal 10 Jambi - Muhammad Emil; Suci Permata Sari (Universitas Batanghari, 2020)
The population of this research is the organizational culture and employee performance of the sales department at PT. Agung Automall Paal 10 Jambi in 2019 an many as 53 people. Using a census that is all the population made responden. Based on the results of simple linear regression analysis, showing the equation Y = 0.844 + 0.682X + e. With a correlation of 44% or 0,440. The value of determination is 0,194 or 19,4%. Where it is intended that the influence of work culture on performance is 19,4% while 80,6% is influenced by other variables not examined in this study. T test value of 3.503 with a significance value of 0.00 <0.05 which is greater than the value of t table of 2.00758.